THE CORRELATION BETWEEN STUDENTS’ LEARNING STYLES AND THE ELEVENTH GRADE STUDENTS’ SPEAKING ABILITY AT SMA N 4 PALEMBANG - Aprilia Sari Rahayu; Eryansyah Eryansyah; Margaretha Dinar Sitinjak (English Review: Journal of English Education, 2022)
The objective of this study was to find out whether or not there was a significant correlation of learning style and the eleventh grade students' speaking ability. In this study, the population was ten students the eleventh grade students of SMA N 4 Palembang. The sample of this study, the researcher used purposive sampling technique. In order to collect the data, in this study used interviews and an oral test from virtual classes. Analyze the data, the researcher used Pearson Product Moment Correlation Coefficient on SPPS. The result speaks interviews with students used the scale rating scores. From these results, the minimum score was 80, the maximum score was 88, and the mean score was 86. Second method was an oral test from virtual classes. In this test the researcher asked the students to tell about the most beautiful place that they have ever visited. Based on the results of the oral test score from virtual classes, the minimum score was 86, the maximum score was 92, and the mean score was 90. It could be concluded, that there was significant correlation between learning style and the eleventh grade students' speaking ability at SMA N 4 Palembang.